ASPEK KELEMBAGAAN DALAM PEMBANGUNAN HUTAN TANAMAN (Some institutional aspects in developing forest plantation) - Apul Sianturi (Pusat Penelitian dan Pengembangan Hasil Hutan, 1993)
Forest as one of natural resources should be managed on sustainable bases for the prosperity of the people. As the number and the income of the people increasrd, the needs or demand for forest products also increased. On the other hand, the increase in population stimulates the decrease in forest land areas. To solve this problem there is a need to increase or optimize the production of forest lands so that the decrease in forest areas does not mean the decrease in forest products.One of the solutions is to establish forest plantations on degraded lands, and to convert natural forests which are less productive to forest plantations which are more productive. Reforestation of degraded forest requires a lot of capital, and financially not profitable, therefore it needs a subsidy, Since degraded forest is not profitable and the locations are scattered in small areas, State Owned Enterprice (BUMN) or Forest Service (Dinas Kehutanan) should do reforestation on these areas. On the other hand conversion of natural forest to forest plantation is financially profitable, therefore it does not need subsidy and can be done by private industry, For this purpose the master plan of natural forest that could be converted to forest plantation should be well prepared. Institutional aspects of these two types of forest plantations are discussed in this report.